Hydatid cyst disease in children: 10-years experience at two tertiary centers from Northeast Anatolia of Turkey - Sener, Ebru; Kurt, Ali (Annals of Medical Research, 2021)
Aim: Hydatid cyst remains a significant health problem in endemic regions such as Turkey. It can be observed at any age, but the diagnosis is usually made at adulthood. The aim of this study was to investigate the epidemiological findings of hydatid cyst cases in the pediatric age group in Turkey. Material and Methods: The records of the patients who received the diagnosis of hydatid cyst in the pathology departments of Ataturk University Faculty of Medicine and Erzurum Regional Training and Research Hospital between 2009–2019 were analyzed retrospectively. Data such as age, sex, location, size and number of cysts of the cases diagnosed with hydatid cyst between 0–16 years of age were analyzed statisticall.Results: Of the 1072 cases diagnosed with hydatid cyst, 32.7% (n=351) were within the age range of 0–16 years, 57.8% (n=203) were male and 42.2% (n=148) were female, with a mean age of 10.8 years (SD: ± 3.5; min: 1, max: 16). In 86.3% (n=303) of the cases, the cyst was found to be located in a single organ, whereas it was located in two different organs in 13.7% (n=48) of the cases. Involvement of the liver and lung was observed in 54.4% (n=191) and 50.4% (n=177) of the cases, respectively. Less involvement was observed in brain (n=10), kidney (n=9), spleen (n=5), retroperitoneal region (n=4), omentum (n=2), nasal cavity (n=1), thoracolumbar region (n=1), tail of the pancreas (n=1) and ulna diaphysis (n=1). In all cases, the mean cyst size was measured to be 7.4 cm (SD: ± 2.9; min: 1.5, max: 17) based on the largest cyst size.Conclusion: Hydatid cyst is also common in the pediatric age group. Hydatid cyst has been found to be more common in males in the pediatric age group in Turkey, with its most common localization being in the liver and lung.